Regional energy effciency programs in Russia: The factors of success - Svetlana Valerievna Ratner; Pavel Ratner (REGION, 2016)
In this paper, we study the reasons for extremely high difference in energy intensity of the Russian regions under different methodological approaches. We compare the most popular measures of state's energy efficiency policy in Russia with best world practices and investigate the factors of their effectiveness. We test the hypothesis that the level of development of regional innovation system determines how the regional economy reacts to the removal of market barriers to energy efficiency. Our findings reveal that in the face of rising electricity prices regions with well-developed regional innovation systems induce technical and other kinds of innovation in the field of energy efficiency, while other regions are not able to reduce their energy intensity. The main practical implementation of the study is that market measures for improvement of energy efficiency do not work in the regions with underdeveloped innovation systems.
Keywords: 330; Environment; Externalities